Ensiling a dry bakery by-product: effect of hydration using acid whey or water associated or not at urea - Rezende, Adauton Vilela De; Rabelo, Carlos Henrique Silveira; Sampaio, Lucas De Moura; HÄrter, Carla Joice; Florentino, Ligiane Aparecida; Paula, Deyvid Wilker; Braga, Tatiane Cristina (UFBA - Universidade Federal da Bahia, 2016)
SUMMARY The objective of this study was to investigate the characteristics of silages prepared with a dry bakery by-product hydrated with acid whey or water associated or not at urea. The trial was a 3 (hydration at three moisture levels: 250, 300, and 350 mL kg−1 of by-product) × 3 (three application rates of urea: 0, 5, and 10 g kg−1 of by-product) × 2 (liquid used at hydration: acid whey or water) factorial arrangement. Mini-silos were used as experimental silos and remained closed for 30 days. Overall, silages hydrated with acid whey had higher (P<0.01) production of lactic (19.6 vs. 18.5 g kg−1 of dry matter [DM]), acetic (2.5 vs. 1.8 g kg−1 of DM) and propionic acid (8.0 vs. 5.4 g kg−1 of DM), and lower (P<0.05) fungi counts (5.35 and 5.01 cfu g−1 of fresh silage) compared to silages hydrated with water. Increased hydration led to the higher production of total acids (P<0.01), decreasing silage pH; but increased hydration reduced DM recovery (P<0.01). Silages hydrated with water and acid whey at 250 mL kg−1 and combined at 5 and 10 g kg−1 of urea exhibited higher DM recovery (P<0.05). Silages of a dry bakery by-product hydrated with acid whey had a better fermentation pattern and could represent a practical strategy to avoid discarding both by-products into environment.

RESUMO O objetivo com este estudo foi investigar as características de silagens preparadas com um resíduo seco de padaria hidratado com soro ácido de leite ou água associado ou não à ureia. O experimento foi conduzido em um arranjo fatorial 3 (três níveis de hidratação: 250, 300 e 350 mL kg−1 de subproduto) × 3 (três níveis de aplicação de ureia: 0, 5 e 10 g kg−1 de subproduto) × 2 (dois líquidos usados na hidratação: soro ácido de leite ou água). Mini silos foram utilizados como silos experimentais e permaneceram fechados por 30 dias. Em geral, silagens hidratadas com soro ácido de leite apresentaram maior (P<0,01) produção de ácido lático (19,6 vs. 18,5 g kg−1 de matéria seca [MS]), ácido acético (2,5 vs. 1,8 g kg−1 de MS) e ácido propiônico (8,0 vs. 5,4 g kg−1 de MS), e menores (P<0,05) contagens de fungos (5,35 e 5,01 ufg g−1 de silagem fresca) comparadas às silagens hidratadas com água. A maior hidratação das silagens aumentou a produção total de ácidos (P<0,01) reduzindo os valores de pH; mas o aumento na hidratação reduziu (P<0,01) a recuperação de MS das silagens. Silagens hidratadas com água e soro ácido de leite a 250 mL kg−1 e combinado com 5 e 10 g kg−1 de ureia exibiram maior (P<0,05) recuperação de MS. Silagens de resíduo seco de padaria hidratadas com soro ácido de leite apresentaram melhor padrão fermentativo, podendo representar uma estratégia prática para evitar o descarte de ambos os subprodutos no ambiente.
Ensilagem de resíduo seco de padaria: efeito da hidratação utilizando soro ácido de leite ou água associada ou não à ureia
Keywords: alternative feed; chemical composition; fungi; lactic acid bacteria; alimento alternativo; bactérias ácido-láticas; composição química; fungos